Implementasi Kurikulum Merdeka terhadap Minat Belajar Siswa dalam Pembelajaran PAI di MTs Yamisa Soreang Bandung - Hidayah, Nur Aini; Rohmah H.S, Siti; Chadidjah, Siti (LP2M STAI Darul Kamal NW Kembang Kerang NTB, 2024)
Islamic Religious Education (PAI) is one of the subjects that has a vital role in shaping the character, morality and spirituality of students in Indonesia. However, the challenge of increasing students' interest in Islamic learning is still the main focus in curriculum development in this country. One of the latest efforts to improve the quality of learning is the implementation of the Independent Curriculum which gives schools and teachers more freedom in designing and implementing learning that is more relevant to student needs. This research aims to explore the impact of implementing the Merdeka Curriculum on students' interest in learning, especially in PAI learning. The research method used in this research is a qualitative approach with data collection techniques through classroom observations, interviews with PAI teachers, and analysis of documents related to the curriculum. The sample for this research consisted of class The research results show that the implementation of the Merdeka Curriculum positively influences students' interest in learning towards PAI. The flexibility provided by the Merdeka Curriculum allows teachers to use more innovative and interesting approaches in teaching, such as the use of interactive learning media and project-based learning methods. In addition, students' active participation in planning and evaluating learning also increases their sense of ownership of the learning process. However, there are several obstacles faced in implementing the Independent Curriculum, such as limited resources and lack of training for teachers in adapting the new curriculum. Therefore, greater support is needed from schools, government and related institutions to improve the quality and success of implementing the Independent Curriculum in PAI learning.